2017
DOI: 10.1007/s00259-017-3650-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra-image referencing for simplified assessment of HER2-expression in breast cancer metastases using the Affibody molecule ABY-025 with PET and SPECT

Abstract: PurposeIn phase I/II-studies radiolabelled ABY-025 Affibody molecules identified human epidermal growth factor receptor 2 (HER2) expression in breast cancer metastases using PET and SPECT imaging. Here, we wanted to investigate the utility of a simple intra-image normalization using tumour-to-reference tissue-ratio (T/R) as a HER2 status discrimination strategy to overcome potential issues related to cross-calibration of scanning devices.MethodsTwenty-three women with pre-diagnosed HER2-positive/negative metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
1
33
0
3
Order By: Relevance
“…HER2 imaging provides an extended scale to the degree of expression contrary to traditional IHC that incorporates the entire range of positive lesions into the ordinal HER2 3+, as shown in the previous studies [11,12,27].…”
Section: Discussionmentioning
confidence: 99%
“…HER2 imaging provides an extended scale to the degree of expression contrary to traditional IHC that incorporates the entire range of positive lesions into the ordinal HER2 3+, as shown in the previous studies [11,12,27].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with immunohistochemical staining of biopsy material demonstrated that the measurement of the maximal uptake value at 2-4 h after injection permits clear discrimination between metastases with 31 and 21 levels of HER2 expression (21). Furthermore, the spleen can be used as an within-image reference tissue to calculate tumorto-spleen ratios, permitting a simple and robust discrimination between metastases with high and low HER2 expression using both PET and SPECT (23) and thus making the diagnosis independent of external hardware calibrations.…”
Section: Affibody Molecules In Radionuclide Imagingmentioning
confidence: 99%
“…SPECT and PET imaging using anti-HER2 Affibody ® molecule [177][178][179][180][181][182] demonstrated the potential of safe, whole-body, and non-invasive "biopsy", allowing receptor expression heterogeneity profiling (Figure 11), in clinical trials with ongoing multicenter Phase II/III one (NCT03655353) [5,[183][184][185][186][187]. [ 68 Ga]Ga-ABY-025 PET-CT presents advantages over [ 111 In]In-ABY-025/SPECT/CT in terms of simpler logistics, higher resolution, higher detection rate, dynamic scanning, and accurate quantification [5,183] potentially allowing staging, prognosis, patient selection, quantification of the receptor expression and therapeutic drug dose estimation, early monitoring of the treatment response and resistance, residual disease, follow-up, and relapse.…”
Section: Impact Of [ 68 Ga]ga-aby-025 Pet-ct On Patient Treatment Manmentioning
confidence: 99%
“…Extraordinary receptor shedding was observed after the start of HER2-targeted therapy wherein most probably the on-going treatment had executed a rapid cytotoxic impact on the metastases with HER2 debris leaking into the blood stream [186]. Liver biopsy after PET examination showed fibrosis and no sign of remaining cancer cells.…”
Section: Impact Of [ 68 Ga]ga-aby-025 Pet-ct On Patient Treatment Manmentioning
confidence: 99%
See 1 more Smart Citation